Impact of Corporate Social Responsibility Policy on Customers' Appetite to Buy Environmental Friendly Products before and After COVID-19 - Gazi, Md. Abu Issa; Al Masud, Abdullah; Hossain, Abu Ishaque; Alam, Mohammad Nurul; Kaium, Md. Abdul; Biswas, Sukanta; Senathirajah, Abdul Rahman bin S (Journal of Ecohumanism, 2024)
Purpose: This research aims to thoroughly examine the diverse effects of corporate social responsibility (CSR) on consumer Appetite, specifically concentrating on consumers' inclination toward purchasing environmentally sustainable products. Notably, we investigate consumers' perceptions across different periods, scrutinizing behavioral shifts before and after the COVID-19 era. Design/Methodology/Approach: Employing a robust empirical strategy, our survey methodology involves a substantial sample of 815 respondents, focusing on the demographic of young consumers in Bangladesh-a dynamic developing nation. The data collection process encompasses a meticulously crafted questionnaire, and our analysis employs the sophisticated framework of structural equation modeling (SEM). Results: Our insights go beyond conventional observations, revealing a nuanced understanding of consumer priorities even in the wake of the pandemic. Consumers consistently prioritize corporate practices related to circular economy principles, the geographical aspects of cloth production, raw material origins, pollution control, workers' rights, and the responsible utilization of recycled materials. Originality/value: This study introduces an original model that significantly contributes to comprehending the impact of CSR on consumer behavior, highlighting its relevance for policymakers in Bangladesh. The implications extend beyond the immediate scope, influencing strategies for integrating eco-friendly products into the broader business environment. Consequences: The empirical findings in this study challenge existing assumptions, emphasizing the pivotal influence of environmental considerations on shaping positive consumer behavior. Beyond superficial observations, this research offers a more sophisticated view of the intricate processes, providing significant insights for academics, industry experts, and businesses.